On-Surface Synthesis and Characterization of [7]Triangulene Quantum Ring - Su, Jie; Fan, Wei; Mutombo, Pingo; Peng, Xinnan; Song, Shaotang; Ondráček, Martin; Golub, Pavlo; Brabec, Jiří; Veis, Libor; Telychko, Mykola; Jelínek, Pavel; Wu, Jishan; et al. (Nano letters, 2021)
The ability to engineer geometrically well-defined antidots in large triangulene homologues allows for creating an entire family of triangulene quantum rings (TQRs) with tunable high-spin ground state, crucial for next-generation molecular spintronic devices. Herein, we report the synthesis of an open-shell [7]triangulene quantum ring ([7]TQR) molecule on Au(111) through the surface-assisted cyclodehydrogenation of a rationally designed kekulene derivative. Bond-resolved scanning tunneling microscopy (BR-STM) unambiguously imaged the molecular backbone of a single [7]TQR with a triangular zigzag edge topology, which can be viewed as [7]triangulene decorated with a coronene-like antidot in the center. Additionally, dI/dV mapping reveals that both inner and outer zigzag edges contribute to the edge-localized and spin-polarized electronic states of [7]TQR. Both experimental results and spin-polarized density functional theory calculations indicate that [7]TQR retains its open-shell septuple ground state (S = 3) on Au(111). This work demonstrates a new route for the design of high-spin graphene quantum rings for future quantum devices.
Keywords: on-surface synthesis; open-shell; antidot engineering; scanning probe microscopy; Triangulene quantum ring